Lattice Strain and Defects Analysis in Nanostructured Semiconductor Materials and Devices by High‐Resolution X‐Ray Diffraction: Theoretical and Practical Aspects (Small Methods 2/2022). Issue 2 (17th February 2022) - Dolabella, Simone; Borzì, Aurelio; Dommann, Alex; Neels, Antonia
Abstract : HR‐XRD Methods In article number 2100932, Neels and co‐workers reviewed important theoretical and practical aspects of HR‐XRD methods. In particular, they focused on nanowires, epitaxial layers, and complex sensor systems. Device fabrication processes affect the crystal lattice coherence, modify lattice strain and defects state, thus impacting on reliability and performance of devices in applications.